Ways of Understanding Wholeness: Place, Christopher Alexander, and Synergistic Relationality - Seamon, David (World futures, 2024)
This article considers architect Christopher Alexander's work in relation to a broader body of research and design focusing on phenomenologies of place and placemaking. The article begins by describing two contrasting ways of understanding wholeness-what are called analytic relationality and synergistic relationality. In analytic relationality, wholes are pictured as sets of arbitrary parts external to each other and among which are located linkages involving stronger and weaker connections and relationships. In contrast, synergistic relationality interprets wholes as dynamic, generative fields that sustain and are sustained by intensive parts that integrally belong to and support the whole. The argument is made that, in terms of synergistic relationality, places can be envisioned as interconnected fields of intertwined relationships gathering and gathered by a lived intimacy between people and world. The article illustrates how Alexander's approach to wholeness assumes a synergistic relationality and contributes to understanding, envisioning, and making places that are whole, robust, and life-enhancing.